Development Success - McCourt, W. author. aut Link
XV, 275 p.
Keywords: This book draws on case studies of social, economic and political governance policies from Latin America, Africa and Asia to examine the circumstances in which governments and societies produce policies that overcome initial opposition to meet their aims.